Cultura y comportamiento informacional en ambientes empresariales y el proceso de inteligencia competitiva - Cavalcante, Luciane de Fátima Beckman; Valentim, Marta Lígia Pomim [UNESP] (My University, 2010)
This article presents and discusses the concepts found in the literature about informational culture, informational behavior, information management, knowledge management and competitive intelligence. It focuses the correlation among those elements and shows, from theliterature analysis, the importance of the informational culture for the development of competitive intelligence in organizations.

Este artículo presenta y discute los conceptos encontrados en la literatura sobre cultura informacional, comportamiento informacional, gestión de la información, gestión del conocimiento e inteligencia competitiva. Enfoca la correlación entre esos elementos y demuestra, a partir del análisis de la literatura, la relevancia de la cultura informacional para el desarrollo de la inteligencia competitiva en organizaciones.
Informational culture and informational behavior in business environments and the process of competitive intelligence
Keywords: Cultura Informacional; Comportamento Informacional; Inteligência Competitiva Organizacional; Ambientes Empresariais; Ambientes Informacionais